Contribution to the design and validation of the national hatchery and fish farm certification system in Ghana, expected to directly benefit 50 hatcheries and 2,000 grow-out farmers - CGIAR Research Program on Policies, Institutions, and Markets (2021)
Based on hatchery and farm assessments by IFPRI, IFPRI and partners drafted a certification protocol for fish seed producers and grow-out fish farmers. Together with Ghana's Fisheries Commission, IFPRI and partners organized national stakeholder validation workshops to validate the protocol. The protocol, which is being finalized, is expected to lead to better quality seeds and safer facilities that will directly benefit roughly 50 hatcheries and 2,000 grow-out farmers and have indirectly benefits for many other value chain actors and consumers.